1992
DOI: 10.1152/jappl.1992.73.6.2470
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma O2 solubility improves O2 uptake of in situ dog muscle working maximally

Abstract: A perfluorocarbon emulsion [formulation containing 90% wt/vol perflubron (perfluorooctylbromide); Alliance Pharmaceutical] was used to increase O2 solubility in the plasma compartment during hyperoxic low hemoglobin concentration ([Hb]) perfusion of a maximally working dog muscle in situ. Our hypothesis was that the increased plasma O2 solubility would increase the muscle O2 diffusing capacity (DO2) by augmenting the capillary surface area in contact with high [O2]. Oxygen uptake (VO2) was measured in isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Significant increases in the levels of arterial pO 2 , along with concomitant decreases in pCO 2 , have been reported in pneumocystis-infected mice (Qureshi et al, 2003) and also, more recently, in MG-inoculated layers (Olanrewaju et al, 2009). An increase in mixed venous pO 2 levels is suggestive of an improvement in global oxygenation status (Hogan et al, 1992). Conversely, high pCO 2 has been reported to suppress the immune response in various human peritoneal cells (Kopernik et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in the levels of arterial pO 2 , along with concomitant decreases in pCO 2 , have been reported in pneumocystis-infected mice (Qureshi et al, 2003) and also, more recently, in MG-inoculated layers (Olanrewaju et al, 2009). An increase in mixed venous pO 2 levels is suggestive of an improvement in global oxygenation status (Hogan et al, 1992). Conversely, high pCO 2 has been reported to suppress the immune response in various human peritoneal cells (Kopernik et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…oxygen bypassing the microcirculation). This view is substantiated by a study that demonstrated an increase of oxygen consumption in a maximally working, in-situ gastrocnemius muscle preparation in anesthetized and haemodiluted dogs after Oxygent administration [12]. It is also substantiated by the fact that increases in mixed venous oxygen partial pressure are generally associated with an Oxygent-dependent improvement in tissue oxygenation, as demonstrated in the heart, brain, muscle, gut and liver [13,14].…”
Section: Preclinical Efficacy Of Second-generation Perfluorocarbon mentioning
confidence: 93%
“…An increase in mixed venous oxygen partial pressure indicates improvement in global oxygenation status [12], rather than shunting of oxygen from arterioles directly into venules (i.e. oxygen bypassing the microcirculation).…”
Section: Preclinical Efficacy Of Second-generation Perfluorocarbon mentioning
confidence: 99%
“…Today, it is believed that under normoxia, red cells resemble distinct O 2 sources within the microcirculation, and that plasma acts primarily as a diffusion barrier (26,27). This becomes even more pronounced during profound dilutional anemia, when the longitudinal distance between red cells is increased within the microvessels and the diffusive resistance of the larger plasma layer increases (7,28). This explains why it is highly desirable to increase the amount of physically dissolved O 2 in plasma: it makes O 2 independent from distinct O 2 sources (i.e., red cells) and changes plasma from a primary diffusion barrier into a ubiquitous source of O 2 .…”
Section: Physiologymentioning
confidence: 99%
“…administration. PFCs are excellent gas solvents and therefore increase the O 2 plasma solubility approximately 20-fold (7). The relationship between O 2 partial pressure and O 2 content in a PFC is linear and obeys Henry's law (8).…”
Section: Introductionmentioning
confidence: 99%